HATS project for lean and smart global logistic: A shipping company case study. (January 2020) - Frontoni, Emanuele; Rosetti, Roberto; Paolanti, Marina; Alves, A.C.
Abstract: Global logistic activities related to e-commerce have become very time dependent in recent years. International couriers face everyday issues related to pick-up time windows, lead times delays, express/normal deliveries management, security and VAT management. There are supply chain management methodologies that, based on lean thinking principles integrated with industry 4.0 concepts, well address these issues. In this paper, a project developed in an Italian shipping company shows the potential of solutions based on these principles and concepts. Main results from this project were lead time reduction and cost reduction, with higher goods security level and a real-time data sharing policy.